Dendritic oligoglycerol regioisomer mixtures and their utility for membrane protein research - Urner, LH; Goltsche, K; Selent, M; Liko, I; Schweder, M-P; Robinson, CV; Pagel, K; Haag, R (Wiley, 2020)
Dendrons are an important class of macromolecules that can be used for a broad range of applications. Recent studies indicated that mixtures of oligoglycerol detergent (OGD) regioisomers are superior over individual regioisomers for protein extraction. The origin of this phenomenon remains puzzling. Here we discuss the synthesis and characterization of dendritic oligoglycerol regioisomer mixtures and their implementation into detergents. We provide experimental benchmarks to support quality control after synthesis and investigate the unusual utility of OGD regioisomer mixtures for extracting large protein quantities from biological membranes. We anticipate that our findings will enable the development of mixed detergent platforms in the future.